Petrology and provenance of the Mesoproterozoic Satakunta formation, SW Finland - Pokki, Jussi; Kohonen, Jarmo; Lahtinen, Raimo; Tapani Rämö, O.; Andersen, Tom (2013)
The Satakunta formation (traditionally referred to as the Satakunta sandstone) is a Mesoproterozoic sequence in a fault-bounded basin within the Palaeoproterozoic Svecofennian Domain, resembling typical red beds with ferric oxides. Compositional variations of the sandstones and associated sediments were studied to consider the subdivision that could represent different basin stages of the formation. In addition, the provenance and especially the presence of rapakivi detritus were scrutinized. We propose a basin evolution model starting from c. 1.60 Ga and ending at 1.27 Ga. The SW margin of the formation, a 591-m-thick 'type section' and the NE margin constitute three distinct lithological assemblages, but a basin-wide stratigraphy cannot be determined. The southwestern margin sequence consists of conglomerates with very well rounded vein-quartz pebbles in a subarkosic matrix. The most voluminous component of the formation is a monotonous medium-grained arkosic arenite with laumontite locally common in the cement. Coarse-grained conglomeratic sandstones are typical rocks in the NE margin of the formation. The source of the southwestern margin sequence had been weathered with a notable loss of Na and Ca and enrichment of detrital heavy minerals. It is geochemically dominated by microcline granites, whereas the source rocks of the northeastern margin sequence had been dominated by a granodioritic composition. The Th/Sc ratio of the sediments indicates that the source is felsic throughout. The 138 detrital zircons analysed for U-Pb geochronology imply an exclusively Svecofennian provenance peaking at 1.88 Ga and recording the erosion of 1.83-1.81 Ga late orogenic granites. The mature SW margin sequence is partly derived from reworked post-Svecofennian platform cover and was deposited during the early stage of the extension related to the anorogenic rapakivi magmatism. The monotonous 'type section' is understood to be a result of a large fluvial braidplain or coastal plain representing a tectonically inactive late ...